Survei Motivasi Atlet PSHT dalam Berlatih Pencak Silat di Padepokan Sidoarjo - Adyatma, Senoaji Moh; Kumaat, Noortje Anita; Juniarto, Pudji; Firmansyah, Awang (Jurnal Porkes, 2024)
The problem in this research is the instability in participation and achievement each year for Sidoarjo PSHT athletes. The aim of the research was to determine the level of motivation of Persaudaraan Setia Hati Terate (PSHT) athletes who practice pencak silat at Padepokan Sidoarjo. The research method used is descriptive quantitative. The research subjects were 25 PSHT athletes aged 14-23 years. Using saturated sample technique. The data collection technique uses the questionnaire method. After the results are obtained, analysis is carried out with the help of SPSS. The results of the study showed that the motivation level of the athletes from the Setia Hati Terate Brotherhood was moderate, obtaining a total score of 2155 and a mean of 86.20. Intrinsic factors amounted to 48% and extrinsic motivation amounted to 28%. In conclusion, the level of motivation of Persaudaraan Setia Hati Terate (PSHT) athletes in practicing pencak silat at Padepokan Sidoarjo is moderate.